Green synthesis and characterization of aluminium fumarate metal-organic framework for heat transformation applications - Kayal, Sibnath (2020)
Microporous materials with higher uptake – offtake difference per adsorption – desorption cycle have great potential to design adsorption assisted chillers, heat pumps and thermal batteries. In this context, we report a green reaction method for synthesizing aluminium fumarate (AlFum) metal-organic framework (MOF). The water uptake on AlFum shows S-shape isotherm curve with sharp increase in uptake – offtake difference in a narrow pressure range. The proposed green synthesized AlFum exhibits higher deliverable energy capacity as compared to that of conventional (dimethylformamide based synthesis) AlFum for adsorptive cooling applications.